2009
DOI: 10.1093/ejo/cjn103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a recently developed nanofiller self-etching primer adhesive with other self-etching primers and conventional acid etching

Abstract: The purpose of this ex vivo study was to compare the bond strengths and modes of failure of brackets bonded with three self-etching products [Adper Prompt L-Pop (3M Espe), Futurabond NR (Voco) and Transbond Plus (3M Unitek)] and a conventional 38 per cent phosphoric acid-etching system Etch-Rite (Pulpdent Corp.) at two different time points. Ninety-six defect-free premolars were randomly allocated to eight groups (n = 12). The etching procedure was carried out according to the manufacturers' instructions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Previous studies 25 , 26 found that the shrinkage of polymerization was affected by the filler content, and another study 7 indicated that greater shrinkage was produced by smaller nanofillers size, which leads to decreased bond strength of self-etch bonding systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies 25 , 26 found that the shrinkage of polymerization was affected by the filler content, and another study 7 indicated that greater shrinkage was produced by smaller nanofillers size, which leads to decreased bond strength of self-etch bonding systems.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles (NPs) of various composition represent the most widespread use of nanotechnology in dentistry 7 . Incorporated nanofillers in adhesives compositions increased resistance against fracture and wear, provided higher dimensional stability and produced higher SBS than conventional adhesives 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the new agents, the addition of nano-fillers with an average particle size of 12 nm increases the penetration of resin monomers and the hybrid layer thickness, which in turn improves the mechanical properties of the bonding systems (42,43). Nano-bonding agents are solutions of nano-fillers, Classification review of dental adhesive systems: from the IV generation to the universal type @ C I C E d i z i o n i I n t e r n a z i o n a l i which produce better enamel and dentin bond strength, stress absorption, and longer shelf life (24).…”
Section: Eighth Generationmentioning
confidence: 99%
“…These new agent from self-etch generations have an acidic hydrophilic monomers and can be easily used on the etched enamel after contamination with saliva or moisture (44). Based on the manufacturer, nano-particles acting as crosslinks, will reduced the dimensional changes (42,43). The type of nano-fillers and the method that these particles are incorporated affect the adhesive viscosity and penetration ability of the resin monomers into collagen fibers spaces (43).…”
Section: Eighth Generationmentioning
confidence: 99%